2014
DOI: 10.1186/2043-7129-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Combined sodium hydroxide and ammonium hydroxide pretreatment of post-biogas digestion dairy manure fiber for cost effective cellulosic bioethanol production

Abstract: Background: The current higher manufacturing cost of biofuels production from lignocellulosics hinders the commercial process development. Although many approaches for reducing the manufacturing cost of cellulosic biofuels may be considered, the use of less expensive feedstocks may represent the largest impact. In the present study, we investigated the use of a low cost feedstock: post-biogas digestion dairy manure fiber. We used an innovative pretreatment procedure that combines dilute sodium hydroxide with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…Other studies have suggested various effects on crop yields with biochar amendments and biochar amendments with fertilizer application including improvements in yields, no change in yields, and decreased yields (Bell & Worrall, 2011; Quilliam et al, 2012; Knowles et al, 2011; Lentz and Ippolito, 2012; Spokas et al, 2012b). Glaser et al (2015) found that biochar added in conjunction with additional fertilizers improved maize yields in sandy soil than fertilizers alone, improving fertilizer use efficiency. These effects should be investigated further before biochar can be recommended for nutrient retention in field application.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have suggested various effects on crop yields with biochar amendments and biochar amendments with fertilizer application including improvements in yields, no change in yields, and decreased yields (Bell & Worrall, 2011; Quilliam et al, 2012; Knowles et al, 2011; Lentz and Ippolito, 2012; Spokas et al, 2012b). Glaser et al (2015) found that biochar added in conjunction with additional fertilizers improved maize yields in sandy soil than fertilizers alone, improving fertilizer use efficiency. These effects should be investigated further before biochar can be recommended for nutrient retention in field application.…”
Section: Resultsmentioning
confidence: 98%
“…A sample of the diluted biochar slurry (1.5 mL) was then poured into the sample cell and the zeta potential was measured following the manufacturer's methodology. Trace element composition was determined by X-ray fluorescence, using a Bruker S8 Tiger wavelength dispersive X-ray fluorescence spectrophotometer following the methodology described by Elumalai et al (2014). These values were found to be as follows: 0.0137% Al, 0.0672% Ca, 0.0194% Cl, 0.0004% Cu, 0.0109% Fe, 0.023% K, 0.0108% Mg, 0.0004% Mn, 0.0208% Na, 0.0041% P, 0.0017% Ru, 0.0016% S, 0.0534% Si, and 0.0007% Zn.…”
Section: Biochar and Soil Characterizationmentioning
confidence: 99%
“…Net energy production was estimated in the range of 5.5-9.6 MJ kg À1 dry raw feed. Although AD effluent glucose yields were acceptable, recovery and reuse of the pretreatment chemicals are required to make this process economically feasible (Elumalai et al, 2014).…”
Section: Pollutantmentioning
confidence: 99%
“…were followed for determination of carbohydrate and lignin (LAP 009), ash (LAP 005) and moisture contents (LAP 012) of rice straw, as described (Elumalai et al, 2014;Elumalai et al, 2012). Fractional compositional analyses including carbohydrate sugars and acid soluble lignin of rice straw before and after catalytic reactions was characterized.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Before scanning, the solid fibers were coated with gold in a smart coater (25 mm stub size) (Elumalai et al, 2014). …”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%